Comprehensive analysis of m7G modification patterns based on potential m7G regulators and tumor microenvironment infiltration characterization in lung adenocarcinoma - Ma, Shouzheng; Zhu, Jun; Wang, Mengmeng; Zhu, Jianfei; Wang, Wenchen; Xiong, Yanlu; Jiang, Runmin; Liu, Lei; Jiang, Tao (Frontiers in Genetics, 2022)
Background: The non-negligible role of epigenetic modifications in tumor microenvironment (TME) complexity and heterogeneity has been demonstrated in recent studies. Nonetheless, the potential regulatory role of N7-methylguanosine (m7G) modification in TME immunological characterization remains unclear. Methods: A comprehensive analysis was performed to explore the m7G modification patterns based on 24 potential m7G regulators in 817 LUAD patients, and the TME landscape in distinct m7G modification patterns were evaluated. The m7Gscore was established based on principal component analysis (PCA) to quantify m7G modification patterns and evaluate the TME cell infiltrating characteristics of individual tumors. Further, correlation analyses of m7Gscore with response to chemotherapy and immunotherapy were performed. Results: We identified three distinct m7G modification patterns with the biological pathway enrichment and TME cell infiltrating characteristics corresponded to immune-desert, immune-inflamed and immune-excluded phenotype, respectively. We further demonstrated the m7Gscore could predict the TME infiltrating characteristics, tumor mutation burden (TMB), response to immunotherapy and chemotherapy, as well as prognosis of individual tumors. High m7Gscore was associated with increased component of immune cell infiltration, low TMB and survival advantage, while low m7Gscore was linked to decreased immune cell infiltration and increased TMB. Additionally, patients with lower m7Gscore demonstrated significant therapeutic advantages. Conclusions: This study demonstrated the regulatory mechanisms of m7G modification on TME formation and regulation of lung adenocarcinoma. Identification of individual tumor m7G modification patterns will contribute to the understanding of TME characterization and guiding more effective immunotherapy strategies.